Un régime monétaire traditionnel contesté par la monnaie d’État : l’histoire du kip au Nord-Laos de 1975 à 2000 - Pierre Alary (Revue de la Régulation)
The Government of the Lao PDR imposed a new economic model in 1986. Reforms sought to promote a “market economy” and to propagate the national currency (kip). Monetizing the economy is a primary objective and at the same time a way to implement the merchandization process. Imposing a new currency is not obvious since it challenges directly the previous monetary order and the social practices it validates. Thus social change sometimes encounters strong resistance and, in Phongsaly, an isolated province north of the Republic, the state relied on taxes to disseminate its currency. The kip has since become important in a context where it originally occupied a place tenuously. It transformed monetary representations, and the traditional currencies and assets with monetary attributes were relegated as goods. The state’s interventions shaped the monetary landscape at the top of which is a suitable currency for the development of commercial exchanges. The political program approved in 1986 is thus achieved.